The military potential of China's commercial technology - Cliff, Roger; Rand eBooks (Santa Monica, CA : RAND, 2001)
China's economy is expected to grow over the next 20 years at a rate that will make it larger than the U.S. economy at the end of that period. This suggests that China has the economic potential to be a U.S. military rival by the year 2020. But can it become such a rival? At present, China's military hardware is largely based on 1950s Soviet technology. To produce weaponry technologically comparable to U.S. weaponry by 2020, China would have to improve its technological capabilities through internal, defense-industry efforts and/or other avenues: direct transfers of military technology from abroad, imports of components and equipment, and diffusion from China's civilian industries. Of these three, the third, diffusion from civilian industries, is the most promising over the long run. This report explores this option, examining China's current commercial technology in eight industries (microelectronics, computers, telecommunications equipment, nuclear power, biotechnology, chemicals, aviation, and space) that have the most potential for supporting military technology development, and assessing the prospects for technological progress (in terms of capabilities, effort, incentives, and institutions) over the next 10 to 20 years. The findings suggest that even though China's military will not be the U.S. military's technological equal by 2020, the U.S. still must prepare for a Chinese military whose capabilities will steadily advance in the next 10 to 20 years and that may develop capabilities in certain "niches" that will present difficulties for the U.S. military in some potential-conflict scenarios.
Introduction -- Background -- Chinab2(Bs Current Civilian Technology -- Potential for Further Progress -- Conclusion.s
"Project Air Force."
Includes bibliographical references (p. 65-77).
Also available on the internet via WWW in PDF format.
Keywords: Defense industries -- China; High technology industries -- Military aspects -- China; Industrial mobilization -- China; Technology and state -- China; China -- Armed Forces; China -- Defenses; China -- Economic conditions -- 1976-2000.; Electronic books